Perancangan User Experience Website Pendaftaran Praktik Kerja Industri (Prakerin) SMKN 2 Malang dengan Metode HCD - Ahmad Fariddudin; Retno Indah Rokhmawati; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SMK Negeri 2 Malang is a vocational high school that runs a program of industrial work practices or commonly called prakerin. The registration process for internship activities at SMK Negeri 2 Malang is without any system assistance and is not centralized or managed by each expertise program. Therefore, SMK Negeri 2 Malang plans to create a website. This study aims to design a user experience so that the system to be built has good results for its users in terms of usability and user experience. The method used in the design is Human-Centered Design (HCD) and the research method uses quantitative descriptive. At the evaluation stage of the solution design the method used is usability testing and filling User Experience Questionnaire (UEQ). The results of the evaluation of the solution design made on student users obtained an effectiveness value of 93,8%, efficiency of 0,068 goals/ second. The results of admin users get an effectiveness value of 93,3%, efficiency 0,136 goals/ second. The results of the overall user satisfaction evaluation of student and admin users get a score of 2,1 in OVERALL. The UEQ results on the attractiveness and dependability obtained the excellent, on the efficiency, perspicuity, stimulation, and novelty obtained the good. These results indicate that the solution design can be accepted with good usability values ​​and user experience values ​​by seeing the value of each aspect or component above the average.